2007
DOI: 10.1063/1.2783271
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electroluminescence efficiency of oxidized amorphous silicon nitride light-emitting devices by modulating Si∕N ratio

Abstract: The authors had reported green-yellow electroluminescence (EL) from N-rich oxidized amorphous silicon nitride (a-SiN:O) light-emitting devices (LEDs) in a previous work. In this work, a significantly enhanced EL intensity was obtained in the LED by employing Si-rich a-SiN:O instead of N-rich a-SiN:O as luminescent active layer. Moreover, the Si-rich a-SiN:O devices also exhibit lower turn-on voltage and the external quantum efficiency is found to be three times higher than that of the N-rich a-SiN:O devices. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…However, little attention has been paid to the electroluminescence (EL) properties of those RE ions embedded either in silicon nitride (Si 3 N 4 ) or silicon-rich silicon nitride (SiN x ) dielectrics. In fact, SiN x -based materials offer considerable advantages over SiO x -based active ones: (i) lower carrier injection barrier at the Si/Si 3 N 4 interface, giving rise to the fabrication of low-voltage light emitting devices (LEDs), 8 (ii) better electrical stability with direct impact on the device operation lifetimes, 9 and (iii) higher effective refractive index for making high quality resonant cavities. 10 Also, we have recently demonstrated the suitability of SiN x , in combination with SiO 2 tunnel layers, as promising candidate for the silicon-solid state lighting.…”
mentioning
confidence: 99%
“…However, little attention has been paid to the electroluminescence (EL) properties of those RE ions embedded either in silicon nitride (Si 3 N 4 ) or silicon-rich silicon nitride (SiN x ) dielectrics. In fact, SiN x -based materials offer considerable advantages over SiO x -based active ones: (i) lower carrier injection barrier at the Si/Si 3 N 4 interface, giving rise to the fabrication of low-voltage light emitting devices (LEDs), 8 (ii) better electrical stability with direct impact on the device operation lifetimes, 9 and (iii) higher effective refractive index for making high quality resonant cavities. 10 Also, we have recently demonstrated the suitability of SiN x , in combination with SiO 2 tunnel layers, as promising candidate for the silicon-solid state lighting.…”
mentioning
confidence: 99%
“…Intrinsic emission has been also observed in SRN ilms [27][28][29][30][31]. For example, an orange emission at 600 nm was observed at room temperature and has been related to the electron-hole pairs' recombination within Si-nps [27].…”
Section: Introductionmentioning
confidence: 74%
“…Also, green emission has been observed in nitrogenrich silicon nitride, which was atributed to radiative recombination in localized states related to Si-O [28]. Some other authors have shown signiicant improvement of the green emission intensity using oxidized silicon-rich nitride [29]. Also, when a silicon nitride ilm is implanted with Si ions, violet and green-yellow emission bands are observed, giving rise to an intense white EL emission [30].…”
Section: Introductionmentioning
confidence: 86%
“…15 Furthermore, electroluminescence (EL) of our a-SiNO films has been demonstrated. 22,23 Based on the investigation of X-ray photoelectron spectroscopy (XPS), we found that the PL from a-SiNO films is corresponding to the O-Si-N bonding configurations. 24 And the characteristic of optical gain related to this kind of O-Si-N bonding states has been also reported.…”
mentioning
confidence: 98%